MiRNA Profiling in Pectoral Muscle Throughout Pre- to Post-Natal Stages of Chicken Development - Chen, Min; Zhang, Shaolan; Xu, Zhongxian; Gao, Jian; Mishra, Shailendra Kumar; Zhu, Qing; Zhao, Xiaoling; Wang, Yan; Yin, Huadong; Fan, Xiaolan; Zeng, Bo; Yang, Mingyao; et al. (Frontiers in Genetics, 2020)
MicroRNA (miRNA) is known to be an important regulator of muscle growth and development. The regulation of microRNA on the skeletal muscle phenotype of animals is mainly achieved by regulating the proliferation and differentiation of myoblasts. In this study, we sequenced a total of 60 samples from 15 developing stages of the pectoral muscle and five other tissues at 300 days of Tibetan chicken. We characterized the expression patterns of miRNAs across muscle developmental stages, and found that the chicken growth and development stage was divided into early-embryonic and late-embryonic as well as postnatal stages. We identified 81 and 21 DE-miRNAs by comparing the miRNA profiles of pectoral muscle of three broad periods and different tissues, respectively; and 271 miRNAs showed time-course patterns. Their potential targets were predicted and used for functional enrichment to understand their regulatory functions. Significantly, GgmiRNA-454 is a time-dependent and tissue-differential expression miRNA. In order to elucidate the role of gga-miRNA-454 in the differentiation of myoblasts, we cultured chicken myoblasts in vitro. The results show that although gga-miRNA-454-3p initiates increase and thereafter decrease during the chicken myoblasts differentiation, it had no effect on primary myoblasts proliferation. Furthermore, we confirm that gga-miRNA-454 inhibits myoblast differentiation by targeting the myotube-associated protein SBF2.